1994
DOI: 10.1210/endo.135.6.7988470
|View full text |Cite
|
Sign up to set email alerts
|

Novel regulation of pregnant human myometrial smooth muscle cell gap junctions by human chorionic gonadotropin.

Abstract: Human myometrium contains hCG/LH receptors. There are fewer of these receptors during labor compared to no labor at preterm or term deliveries. Exogenous hCG can directly inhibit oxytocin-stimulated human myometrial contractions. These findings suggest that hCG may directly maintain myometrial quiescence during pregnancy. As maintenance of uterine quiescence may involve down-regulation of myometrial gap junctions, we investigated the effect of hCG on connexin-43 (CX-43) gene expression from RNA to protein and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Different hypotheses have been suggested, such as a decrease in intracellular free calcium concentrations, down-regulation of myometrial gap junctions, activation of BKCa channels, as well as inhibition of uterotonic agents [8,24,26,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different hypotheses have been suggested, such as a decrease in intracellular free calcium concentrations, down-regulation of myometrial gap junctions, activation of BKCa channels, as well as inhibition of uterotonic agents [8,24,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, since the discovery of LH/hCG receptors in pig uterus by Ziecik et al, it is well known that gonadotropins receptors are present not only in male and female gonads, but also in extragonadal reproductive tissues both in humans and domestic animals [7][8][9][10][11]. LH/hCG receptors are expressed in the myometrium of the woman, pig, rabbit and cow, and their expression is dependent on the stage of the estrous cycle, and can be modulated by steroid hormones [7,9,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hCG is an inhibitor of myometrial contractions, antagonizes the oxytocin actions and the mechanisms of action are rather fairly well defined. [2][3][4]16 It has minor side effects that do not generally require medical attention. In addition, it is cheap and can be made even cheaper by scaling up the production of recombinant hormone.…”
Section: 14mentioning
confidence: 99%
“…In vitro and in vivo human studies have demonstrated that the activation of LHR in uterine and Fallopian tube results in numerous changes that are required for pregnancy initiation (21,22), maintenance (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) and for parturition to occur in a timely manner (37).…”
Section: Introductionmentioning
confidence: 99%
“…The results of other studies suggested that estradiol promotes LHR synthesis in the epithelium and smooth muscle and, along with LH, causes the relaxation of the porcine oviduct, especially during the periovulatory stage of the oestrous cycle (10,(30)(31)(32)(33)(34)(35)(36)(37)(38). The results of an animal study indicated that LHR can control oviductal contractions directly and may be partially responsible for the relaxation of the isthmus during fertilization in pigs (10).…”
Section: Introductionmentioning
confidence: 99%